2012
DOI: 10.1186/1471-2407-12-6
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review: conservative treatments for secondary lymphedema

Abstract: BackgroundSeveral conservative (i.e., nonpharmacologic, nonsurgical) treatments exist for secondary lymphedema. The optimal treatment is unknown. We examined the effectiveness of conservative treatments for secondary lymphedema, as well as harms related to these treatments.MethodsWe searched MEDLINE®, EMBASE®, Cochrane Central Register of Controlled Trials®, AMED, and CINAHL from 1990 to January 19, 2010. We obtained English- and non-English-language randomized controlled trials or observational studies (with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
80
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(86 citation statements)
references
References 43 publications
4
80
0
2
Order By: Relevance
“…The publications on lymphedema treatment received much criticism regarding methodological rigor, lack of standardized protocols and uncontrolled studies 9,30,31 . Most clinical trials focus on results and discussion on reducing lymphedema volume, without more detailed analysis, and assess few variables in addition to limb volume.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The publications on lymphedema treatment received much criticism regarding methodological rigor, lack of standardized protocols and uncontrolled studies 9,30,31 . Most clinical trials focus on results and discussion on reducing lymphedema volume, without more detailed analysis, and assess few variables in addition to limb volume.…”
Section: Discussionmentioning
confidence: 99%
“…Frequently the literature has reported the difficulties in relating results of statistical tests with what would in fact be clinically significant 7,[27][28][29][30][31] . Although is not clear in the literature that volume change metrics are minimally important for patients, CDT appears as an alternative to reduce the suffering of patients with peripheral lymphedema, since there is a reduction in varied percentages, even if they are not statistically significant signifiers.…”
Section: Discussionmentioning
confidence: 99%
“…1,3 Moreover, previous reports suggested that clinicians had often shown inadequate knowledge and lack of interest in the evidence-based management of lymphoedema, 15 particularly lymphoedema secondary to non-breast malignancies. [16][17][18][19] Standardised assessments of LLL exist (e.g. the International Society of Lymphology lymphoedema staging system 10 ) and are routinely used by specialist management units of lymphoedema.…”
Section: Introductionmentioning
confidence: 99%
“…7 When analyzing the diagnostic of lymphedema, most of the studies considered differences between homolateral and contralateral limbs above 10% and/or 200 mL, as was proposed in the present study.…”
Section: Discussionmentioning
confidence: 99%